2015
DOI: 10.1039/c5lc00313j
|View full text |Cite
|
Sign up to set email alerts
|

A ready-to-use, versatile, multiplex-able three-dimensional scaffold-based immunoassay chip for high throughput hepatotoxicity evaluation

Abstract: Hydrogel as three-dimensional (3D) substrate has been employed in miniaturized high throughput protein detection platforms to increase the number of effective antibodies and signal augmentation. However, the high water content of the hydrogel can dilute samples and create barrier to mass transfer, limiting hydrogel height to several microns in most platforms. Moreover, these platforms cannot achieve widespread use in common laboratories as they usually rely heavily on expensive robotic liquid handlers and cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Ovarian cancer cells also show increased chemoresistance when grown as 3D spheroids compared to 2D culture [ 139 , 140 , 141 , 142 ]. It has now been established that 3D scaffolds generally better imitate the in vivo tumor microenvironment necessary for modelling cancer cell-ECM interactions and also for cancer cell-drug screening assays [ 136 , 143 , 144 , 145 , 146 , 147 ]. The interaction between cancer cells and their surrounding microenvironment plays a significant role in the acquisition of drug resistance in many cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer cells also show increased chemoresistance when grown as 3D spheroids compared to 2D culture [ 139 , 140 , 141 , 142 ]. It has now been established that 3D scaffolds generally better imitate the in vivo tumor microenvironment necessary for modelling cancer cell-ECM interactions and also for cancer cell-drug screening assays [ 136 , 143 , 144 , 145 , 146 , 147 ]. The interaction between cancer cells and their surrounding microenvironment plays a significant role in the acquisition of drug resistance in many cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a microfluidic device with in‐channel micropatterning of antibodies enables highly sensitive and fast detection of biomolecules secreted from cells with samples of a few microliters. In addition, hydrogel microarrays have been employed as a reproducible and reliable high‐throughput immunoassay system . For instance, antibody‐containing lyophilized hydrogels were developed to evaluate hepatotoxicity responses to introduced drugs .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hydrogel microarrays have been employed as a reproducible and reliable high‐throughput immunoassay system . For instance, antibody‐containing lyophilized hydrogels were developed to evaluate hepatotoxicity responses to introduced drugs . By sandwiching cell culture chip microarrays and drug‐loaded immunochips, cell secreted biomarkers could be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term culture was maintained as long as 30 days at single cell level, with the ability to retrieve any cell of interest for further examination. Collagen based 3D microtissue culture models for cell viability assessment [27] or immunoassay of cytotoxicity [28] under drug stimulation were also reported, which were compatible to microplate reader. This platform provides a high throughput and quantitative method for drug screening and better prediction of drug efficacy at the tissue level.…”
Section: Cell Culture On Chipmentioning
confidence: 99%